Carbon-ceramic material, carbon-ceramic brake disc and preparation method of carbon-ceramic brake disc
By introducing rare earth oxides into carbon ceramic materials and preparing them by chemical vapor infiltration deposition and impregnation methods, combined with mechanical processing and siliconization treatment, the problems of complex production process and poor mechanical properties of existing carbon ceramic brake discs are solved, and the performance is achieved Preparation of excellent carbon ceramic brake discs.
Patent Information
- Application Number
- CN202310847987.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing carbon ceramic brake disc production process is complex and the material mechanical properties are poor, making it difficult to meet the needs of lightweight automotive brake discs.
A carbon ceramic material containing 25-40wt% carbon, 60-70wt% silicon carbide, 0.5-3.5wt% residual silicon and 1-3wt% rare earth oxide is prepared by chemical vapor infiltration deposition and impregnation methods , combined with mechanical processing and siliconization treatment, to prepare a carbon ceramic brake disc with excellent performance.
The compressive, bending and interlaminar shear strength of the carbon ceramic material is improved, the density is between 1.2-2.8g/cm3, the mechanical properties are significantly improved, and it is suitable for the application of lightweight automobile brake discs.
Smart Images

Figure BDA0004337725850000151 
Figure BDA0004337725850000152 
Figure BDA0004337725850000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon ceramic materials, and in particular to a carbon ceramic material, a carbon ceramic brake disc and a preparation method thereof. Background Art
[0002] Carbon ceramic materials have the characteristics of high temperature resistance, low thermal expansion coefficient, low density, high strength and high hardness. They are expected to replace metal materials and become the preferred raw material for the preparation of lightweight automotive brake discs in the future, with huge market potential.
[0003] At present, the preparation process of carbon ceramic materials mainly includes chemical vapor infiltration deposition (CVI), precursor impregnation cracking method, melt siliconization method, etc. CN109095929B proposes a method for preparing carbon ceramic brake discs using a needle-punched fiber preform as a blank, a vapor deposition method, a precursor impregnation method, and a combined process of melt siliconization, using polymethylsilane as an impregnation liquid, and increasing the thermal conductivity of the composite material by introducing metal elements. However, repeated impregnation and carbonization operations do not significantly increase the density, and closed pores will be formed in the pores originally generated by carbonization, reducing the mechanical properties.
[0004] CN109437955B discloses a method of directly using short-cut carbon fibers and resin to form a blank at low temperature, and then subjecting it to carbonization and siliconization to obtain a carbon-ceramic composite material. This method is simple in process, but siliconization is directly performed after carbonization, and the single pyrolytic carbon protective layer is relatively weak, which cannot provide effective protection for the carbon fibers during the siliconization process, resulting in a decrease in material performance.
[0005] Therefore, it is urgent to provide a carbon ceramic material with simple production process and excellent performance, as well as a carbon ceramic brake disc and its preparation. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of complex production process and poor mechanical properties of carbon-ceramic brake discs in the prior art, and to provide a carbon-ceramic material with simple production process and excellent performance, as well as a carbon-ceramic brake disc and its preparation.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a carbon ceramic material, wherein the carbon ceramic material comprises: 25-40wt% carbon, 60-70wt% silicon carbide, 0.5-3.5wt% residual silicon, and 1-3wt% rare earth oxide; wherein the carbon ceramic material has a compressive resistance of 190-270MPa, a flexural resistance of 160-250MPa, and an interlaminar shear strength of 60-95MPa.
[0008] A second aspect of the present invention provides a method for preparing a carbon-ceramic brake disc, wherein the method comprises the following steps:
[0009] (1) performing a deposition process on the preform to obtain a deposition material;
[0010] (2) impregnating the deposited material in an impregnation liquid to obtain an impregnated material; wherein the impregnation liquid contains a silane coupling agent and a rare earth oxide;
[0011] (3) curing the impregnated material to obtain a cured material;
[0012] (4) carbonizing the solidified material to obtain a carbonized material;
[0013] (5) machining the carbonized material to obtain a brake disc blank;
[0014] (6) The brake disc blank is mixed with silicon powder and then subjected to siliconizing treatment to obtain a carbon ceramic brake disc.
[0015] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0016] 1) A carbon ceramic material provided in the present invention contains rare earth oxides. The rare earth oxides, as sintering aids for silicon carbide, can improve the densification degree of silicon carbide, thereby helping to improve the strength and hardness of the carbon ceramic material; the carbon ceramic material modified by rare earth oxides has a compressive strength of 190-270 MPa, a bending strength of 160-250 MPa, an interlaminar shear strength of 60-95 MPa, and a density of 1.2-2.8 g / cm 3 , excellent mechanical properties and good market application prospects;
[0017] 2) In the preparation method of a carbon ceramic brake disc provided in the present invention, the addition of a silane coupling agent can, on the one hand, improve the uniformity of the distribution of silicon carbide on the carbon ceramic brake disc and reduce the residual silicon content on the brake disc after siliconization; on the other hand, it can enhance the bonding strength between silicon carbide, silicon powder, rare earth oxide and resin, avoid the sedimentation of inorganic fillers, and effectively improve the high temperature resistance of the resin, thereby increasing the curing temperature, improving the curing effect, ensuring that the preform can shrink evenly during the subsequent curing and carbonization process, without cracking, deformation, bubbling and large pores, and ensuring the compactness of the carbon ceramic brake disc;
[0018] 3) The method for preparing a carbon-ceramic brake disc provided in the present invention only requires one chemical vapor infiltration deposition and impregnation operation, which can avoid repeated operations, significantly shorten the preparation time, and improve the mechanical properties of the carbon-ceramic brake disc. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] A first aspect of the present invention provides a carbon ceramic material, wherein the carbon ceramic material comprises: 25-40wt% carbon, 60-70wt% silicon carbide, 0.5-3.5wt% residual silicon, and 1-3wt% rare earth oxide; wherein the carbon ceramic material has a compressive strength of 190-270MPa, a flexural strength of 160-250MPa, and an interlaminar shear strength of 60-95MPa.
[0021] In one embodiment of the present invention, the carbon content can be 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, and any value in the range formed by any two of these point values.
[0022] In one embodiment of the present invention, the content of silicon carbide can be 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, and any value in the range formed by any two of these point values.
[0023] In one embodiment of the present invention, the residual silicon content can be 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, and any value in the range formed by any two of these point values.
[0024] In one embodiment of the present invention, the content of rare earth oxide can be 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3wt%, and any value in the range formed by any two of these point values.
[0025] In one embodiment of the present invention, the rare earth oxide is selected from one or more of cerium oxide, yttrium oxide, lanthanum oxide, neodymium oxide, praseodymium oxide, and samarium oxide, preferably cerium oxide.
[0026] Among them, in the present invention, the inventors have found through research that the introduction of rare earth metal oxides into carbon ceramic materials can serve as sintering aids to make the silicon carbide in the carbon ceramic material more dense, which helps to improve the strength and hardness of the carbon ceramic material.
[0027] In one embodiment of the present invention, the carbon ceramic material has a compressive strength of 250-265 MPa, a flexural strength of 240-250 MPa, and an interlaminar shear strength of 85-90 MPa.
[0028] In one embodiment of the present invention, the density of the carbon ceramic material is 1.2-2.8 g / cm 3 , preferably 2.1-2.3 g / cm 3 .
[0029] A second aspect of the present invention provides a method for preparing a carbon-ceramic brake disc, wherein the method comprises the following steps:
[0030] (1) performing a deposition process on the preform to obtain a deposition material;
[0031] (2) impregnating the deposited material in an impregnation liquid to obtain an impregnated material; wherein the impregnation liquid contains a silane coupling agent and a rare earth oxide;
[0032] (3) curing the impregnated material to obtain a cured material;
[0033] (4) carbonizing the solidified material to obtain a carbonized material;
[0034] (5) machining the carbonized material to obtain a brake disc blank;
[0035] (6) The brake disc blank is mixed with silicon powder and then subjected to siliconizing treatment to obtain a carbon ceramic brake disc.
[0036] In step (1):
[0037] In one embodiment of the present invention, the density of the preform is 0.1-0.6 g / cm 3 , preferably 0.2-0.3 g / cm 3 .
[0038] The method for preparing the carbon ceramic material provided in the present invention can prepare a high-density carbon ceramic material by using a low-density preform as a raw material and combining it with a subsequent impregnation liquid.
[0039] In one embodiment of the present invention, the preform is selected from carbon fiber cloth, and is formed by alternately laying a single layer of non-woven cloth and a web through a step-by-step needling method.
[0040] In one embodiment of the present invention, the number of alternating layers of the single-layer nonwoven fabric and the web is selected from 30-80 layers, preferably 40-60 layers.
[0041] Among them, in the present invention, the number of alternating layers is 30-80, which can meet the size requirements of the brake disc on the one hand, and ensure the penetration depth of carbon deposition on the other hand, thereby further improving the mechanical properties of the brake disc.
[0042] In one embodiment of the present invention, the deposition treatment is selected from chemical vapor infiltration deposition, and the operating conditions of the chemical vapor infiltration deposition method include: the deposition carbon source is selected from one or more of methane, propane, and propylene, preferably methane; the deposition diluent gas is selected from nitrogen and / or argon, preferably nitrogen.
[0043] In one embodiment of the present invention, the flow rate of the deposited carbon source is 30-80 L / min, preferably 60-70 L / min; the flow rate of the deposited dilution gas is 5-25 L / min, preferably 10-15 L / min.
[0044] In one embodiment of the present invention, the operating conditions of the chemical vapor infiltration deposition method also include: the number of depositions is 1, the deposition temperature is 900-1200°C, preferably 1050-1080°C; the deposition pressure is 5-30KPa, preferably 5-10KPa; the deposition time is 50-200h, preferably 90-150h.
[0045] Among them, in the present invention, the preform is deposited by chemical vapor infiltration deposition, and deposited carbon can be generated on the carbon fibers of the preform by pyrolysis, which can enhance the bonding strength between the deposited carbon and the carbon fibers in the preform, making the deposited carbon less likely to fall off. The preform is deposited only once at high temperature, which can improve the effect of the subsequent impregnation treatment.
[0046] In step (2):
[0047] In one embodiment of the present invention, the silane coupling agent is selected from one or more of methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, methylethyldiethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3,4-epoxycyclohexylmethyltrimethoxysilane and 3,4-epoxycyclohexylmethyltriethoxysilane.
[0048] Among them, in the present invention, the addition of silane coupling agent can, on the one hand, improve the uniformity of the distribution of silicon carbide on the carbon-ceramic brake disc and reduce the residual silicon content on the brake disc after siliconization; on the other hand, it can enhance the bonding strength between silicon carbide, silicon powder, rare earth oxide and resin, avoid the sedimentation of inorganic fillers, and effectively improve the high temperature resistance of the resin, thereby increasing the curing temperature, improving the curing effect, ensuring that the preform can shrink evenly during the subsequent curing and carbonization process, without cracking, deformation, bubbling and large pores, thereby ensuring the density of the carbon-ceramic brake disc.
[0049] In one embodiment of the present invention, the rare earth oxide is selected from one or more of cerium oxide, yttrium oxide, lanthanum oxide, neodymium oxide, praseodymium oxide, and samarium oxide, preferably cerium oxide.
[0050] In one embodiment of the present invention, the impregnation liquid further comprises a resin, a curing agent, silicon powder, silicon carbide powder and a solvent; wherein the resin is selected from one or more of phenolic resin emulsion, furan resin emulsion and epoxy resin emulsion, preferably epoxy resin emulsion; the curing agent is selected from one or more of urotropine, ethylenediamine and diethylenetriamine, preferably urotropine; and the solvent is selected from ethanol and / or ethylene glycol.
[0051] Among them, the present invention does not specifically limit the phenolic resin emulsion, furan resin emulsion, and epoxy resin emulsion, and the common commercially available phenolic resin emulsion, furan resin emulsion, and epoxy resin emulsion with a solid content of more than 60% can be used in the present invention. In the present invention, the resin introduced by impregnation in the deposition material is partially converted into carbon after curing and carbonization treatment, and partially reacts with the silane coupling agent to convert into silicon carbide, which can not only further increase the density of the material, but also effectively protect the carbon fiber from being damaged during the siliconization process, and can also reduce the number of deposition or impregnation operations, shortening the production cycle.
[0052] In one embodiment of the present invention, the impregnation liquid contains, by mass, 9000 parts of resin, 400-1000 parts of silane coupling agent, 50-300 parts of rare earth oxide, 700-1100 parts of curing agent, 900-1600 parts of silicon powder, 900-1600 parts of silicon carbide powder and 100-300 parts of solvent.
[0053] In a preferred embodiment of the present invention, the impregnation solution contains, by mass, 9000 parts of resin, 600-800 parts of silane coupling agent, 100-200 parts of rare earth oxide, 800-900 parts of curing agent, 1100-1400 parts of silicon powder, 1100-1400 parts of silicon carbide powder and 150-250 parts of solvent.
[0054] In one embodiment of the present invention, the impregnation is carried out at room temperature and under vacuum, and the impregnation time is 1-4 hours, preferably 1.5-2.5 hours.
[0055] In one embodiment of the present invention, after the impregnation is completed, the deposited material is taken out from the impregnation liquid and dried naturally to obtain an impregnated material, wherein the natural drying time may be 1-5 hours.
[0056] In one embodiment of the present invention, the leaching treatment is performed once. In the present invention, the immersion only needs to be performed once, without repeated operation, which can significantly reduce the closed porosity, so that the immersion liquid can penetrate into the interior of the preform as much as possible, improve the dispersion uniformity of carbon and silicon carbide, and thus improve the mechanical properties of the carbon ceramic brake disc.
[0057] In step (3):
[0058] In one embodiment of the present invention, the curing treatment is carried out under hot pressing conditions, wherein the hot pressing temperature is 200-350°C, preferably 250-300°C; the hot pressing pressure is 5-15MPa, preferably 8-12MPa; and the hot pressing time is 1-3h, preferably 1.5-2.5h.
[0059] Among them, in the present invention, when the hot pressing temperature is preferably 250-300° C., on the one hand, it can promote the complete curing of the resin, and on the other hand, it can promote the volatilization of the solvent in the pores to prevent internal cracks caused by solvent volatilization in the subsequent carbonization process.
[0060] In step (4):
[0061] In one embodiment of the present invention, the carbonization treatment is performed under the protection of an inert gas, wherein the inert gas refers to a gas that does not chemically react with the curing material, for example, nitrogen.
[0062] In one embodiment of the present invention, the operating conditions of the carbonization treatment include: carbonization temperature of 800-1000°C, preferably 850-950°C; carbonization pressure of 100-500Pa, preferably 200-400Pa; carbonization time of 2-6h, preferably 3.5-4.5h.
[0063] In step (5):
[0064] In one embodiment of the present invention, the machining includes the aperture size requirements of the brake disc, bolt holes and positioning holes are machined on the surface, and cooling channels are milled on the outer ring, leaving a machining allowance of 1-3 mm in the thickness direction to obtain a blank.
[0065] The present invention does not impose any special limitation on mechanical processing, and the carbonized material can be processed into a brake disc blank according to actual needs and in accordance with known methods.
[0066] In step (6):
[0067] In one embodiment of the present invention, the particle size of the silicon powder is 10-100 μm, preferably 30-60 μm; the purity of the silicon powder is ≥98%, preferably 99-99.9%.
[0068] In one embodiment of the present invention, the mass of the silicon powder is 1-2.5 times, preferably 1-1.5 times, that of the brake disc blank.
[0069] In one embodiment of the present invention, the mixing is preferably performed by burying the brake disc blank in the silicon powder.
[0070] In one embodiment of the present invention, the operating conditions of the siliconizing treatment include: the siliconizing treatment temperature is 1450-1800° C., preferably 1550-1650° C.; the siliconizing treatment time is 1-6 hours, preferably 2-3 hours.
[0071] In the present invention, step (5) is omitted and the carbonized material is directly subjected to siliconization treatment to obtain the carbon ceramic material described in the first aspect of the present invention.
[0072] A third aspect of the present invention provides a carbon-ceramic brake disc prepared by the preparation method described in the first aspect of the present invention.
[0073] The present invention will be described in detail below through examples.
[0074] The preform A is formed by alternately laying 50 layers of single-layer non-woven fabric and mesh tire by step-by-step needle punching method, with a density of 0.3g / cm 3 Preform B is formed by alternating 40 layers of single-layer non-woven fabric and mesh tire by step-by-step needle punching method, with a density of 0.25 / cm 3 .
[0075] Silane coupling agents: KH550, KH 560 (brand of the Chinese Academy of Sciences), purchased from Dongguan Shanyi Plastic Chemical Co., Ltd.
[0076] Epoxy resin emulsion: water-based epoxy resin produced by Guangzhou Epoxy Material Technology Co., Ltd., brand GW-7520.
[0077] Phenolic resin emulsion: a commercial product with brand number 2123 produced by Shenzhen Yoshida Chemical Co., Ltd.
[0078] Furan resin emulsion: a commercial product of Hebei Hongye Chemical Co., Ltd. with a brand name of sz001. Silicon powder is a commercial product of Anyang Qianyu Metallurgical Materials Co., Ltd. with a brand name of Si553, with a particle size of 40 μm and a purity of 99.3%.
[0079] The silicon carbide powder is a commercial product of Shandong Liang New Material Technology Co., Ltd. with the brand name LA6352, a particle size of 1-2 μm, and a purity of 99.6%.
[0080] Rare earth oxides are products of the rare earth oxide series of Beijing Zhongke Keyou Technology Co., Ltd., with a particle size of 3-5nm.
[0081] Example 1
[0082] (1) The preform A is placed in a carbon-carbon deposition furnace and deposited by chemical vapor infiltration deposition, wherein the deposition carbon source is methane, the deposition diluent is nitrogen, the methane is 60 L / min, the nitrogen is 10 L / min, the deposition temperature is 1060 ° C, the deposition time is 120 h, the deposition pressure is 5 KPa, and the density after deposition is 1.0 g / cm 3 Deposition materials;
[0083] (2) immersing the above-mentioned deposited material in an impregnation liquid, standing it in a vacuum environment at room temperature for 2 hours, and then taking it out and drying it naturally for 1 hour to obtain an impregnated material; wherein the impregnation liquid includes 9000g of epoxy resin emulsion, 800g of KH550, 200g of cerium oxide, 900g of urotropine, 1350g of silicon powder, 1350g of silicon carbide powder and 200g of ethanol;
[0084] (3) The impregnated material was placed in a hot press for curing at a temperature of 300°C, a pressure of 10 MPa, and a time of 2.5 h to obtain a density of 1.7 g / cm 3 The curing material;
[0085] (4) The solidified material was then placed in a high-temperature furnace with nitrogen as the protective atmosphere at 900°C and 300 Pa for 4 hours for carbonization treatment to obtain a density of 1.4 g / cm 3 Carbonized materials;
[0086] (5) The carbonized composite material is machined to form bolt holes and positioning holes on the surface according to the aperture size requirements of the brake disc, and a cooling channel is milled on the outer ring, leaving a machining allowance of 2 mm in the thickness direction to obtain a brake disc blank;
[0087] (6) The above brake disc blank is placed in a graphite crucible and covered with silicon powder, the mass of which is 1.2 times that of the brake disc blank. The crucible is then placed in a high-temperature furnace and kept at 1650°C for 3 hours under vacuum for siliconization treatment to obtain a density of 2.1 g / cm 3 Carbon ceramic brake discs.
[0088] Example 2
[0089] (1) The preform A is placed in a carbon-carbon deposition furnace and deposited by chemical vapor infiltration deposition, wherein the deposition carbon source is methane, the deposition diluent is nitrogen, the methane is 65 L / min, the nitrogen is 10 L / min, the deposition temperature is 1065 ° C, the deposition time is 110 h, the deposition pressure is 5 KPa, and the density after deposition is 0.9 g / cm 3 Deposition materials;
[0090] (2) immersing the above-mentioned deposited material in an impregnation liquid, standing it in a vacuum environment at room temperature for 2 hours, and then taking it out and drying it naturally for 1 hour to obtain an impregnated material; wherein the impregnation liquid includes 9000g of epoxy resin emulsion, 700g of KH550, 150g of cerium oxide, 900g of urotropine, 1200g of silicon powder, 1200g of silicon carbide powder and 200g of ethanol;
[0091] (3) The impregnated material was placed in a hot press for curing at a temperature of 260°C, a pressure of 10 MPa, and a time of 2 h to obtain a density of 1.6 g / cm 3 The curing material;
[0092] (4) The solidified material was then placed in a high-temperature furnace with nitrogen as the protective atmosphere and kept at 900°C and 300Pa for 4 hours for carbonization treatment to obtain a density of 1.3 g / cm 3 Carbonized materials;
[0093] (5) The carbonized composite material is machined to form bolt holes and positioning holes on the surface according to the aperture size requirements of the brake disc, and a cooling channel is milled on the outer ring, leaving a machining allowance of 2 mm in the thickness direction to obtain a brake disc blank;
[0094] (6) The above brake disc blank is placed in a graphite crucible and covered with silicon powder, the mass of which is 1.3 times that of the brake disc blank. The crucible is then placed in a high-temperature furnace and kept at 1700°C for 3 hours under vacuum for siliconization treatment to obtain a density of 2.2 g / cm 3 Carbon ceramic brake discs.
[0095] Example 3
[0096] (1) The preform is placed in a carbon-carbon deposition furnace and deposited by chemical vapor infiltration deposition, wherein the deposition carbon source is methane, the deposition diluent is nitrogen, the methane is 70 L / min, the nitrogen is 10 L / min, the deposition temperature is 1070 ° C, the deposition time is 100 h, the deposition pressure is 5 KPa, and the density after deposition is 1.1 g / cm 3 Deposition materials;
[0097] (2) immersing the above-mentioned deposited material in an impregnation liquid, standing it for 2 hours in a vacuum environment at room temperature, and then taking it out and drying it naturally for 1 hour to obtain an impregnated material; wherein the impregnation liquid includes 9000g of epoxy resin emulsion, 600g of KH550, 100g of cerium oxide, 900g of urotropine, 1100g of silicon powder, 1100g of silicon carbide powder and 200g of ethanol;
[0098] (3) The impregnated material was placed in a hot press for curing at a temperature of 280°C, a pressure of 10 MPa, and a time of 1.5 h to obtain a density of 1.8 g / cm 3 The curing material;
[0099] (4) The solidified material was then placed in a high-temperature furnace with nitrogen as the protective atmosphere at 900°C and 300 Pa for 4 hours for carbonization treatment to obtain a density of 1.5 g / cm 3 Carbonized materials;
[0100] (5) The carbonized composite material is machined to form bolt holes and positioning holes on the surface according to the aperture size requirements of the brake disc, and a cooling channel is milled on the outer ring, leaving a machining allowance of 2 mm in the thickness direction to obtain a brake disc blank;
[0101] (6) The above brake disc blank is placed in a graphite crucible and covered with silicon powder, the mass of which is 1.5 times that of the brake disc blank. The crucible is then placed in a high-temperature furnace and kept at 1600°C for 3 hours under vacuum for siliconization treatment to obtain a density of 2.3 g / cm 3 Carbon ceramic brake discs.
[0102] Example 4
[0103] (1) The preform is placed in a carbon-carbon deposition furnace and deposited by chemical vapor infiltration deposition, wherein the deposition carbon source is methane, the deposition diluent is nitrogen, the methane is 35 L / min, the nitrogen is 10 L / min, the deposition temperature is 1150 ° C, the deposition time is 72 h, and the deposition pressure is 20 KPa. After deposition, the density is 0.6 g / cm 3 Deposition materials;
[0104] (2) immersing the above-mentioned deposited material in an impregnation solution, standing it for 2 hours in a vacuum environment at room temperature, and then taking it out and drying it naturally for 1 hour to obtain an impregnated material; wherein the impregnation solution includes 9000g of phenolic resin emulsion, 500g of KH550, 250g of lanthanum oxide, 800g of ethylenediamine, 1000g of silicon powder, 1000g of silicon carbide powder and 200g of ethanol;
[0105] (3) The impregnated material was placed in a hot press for curing at a temperature of 220°C, a pressure of 15 MPa, and a time of 3 h to obtain a density of 1.4 g / cm 3 The curing material;
[0106] (4) The solidified material was then placed in a high temperature furnace with nitrogen as the protective atmosphere at 900°C and 300 Pa for 4 hours for carbonization treatment to obtain a density of 1.0 g / cm 3 Carbonized materials;
[0107] (5) The carbonized composite material is machined to form bolt holes and positioning holes on the surface according to the aperture size requirements of the brake disc, and a cooling channel is milled on the outer ring, leaving a machining allowance of 2 mm in the thickness direction to obtain a brake disc blank;
[0108] (6) The above brake disc blank is placed in a graphite crucible and covered with silicon powder, the mass of which is twice that of the brake disc blank. The crucible is then placed in a high-temperature furnace and kept at 1700°C for 3 hours under vacuum for siliconization treatment to obtain a density of 1.9 g / cm 3 Carbon ceramic brake discs.
[0109] Example 5
[0110] (1) The preform is placed in a carbon-carbon deposition furnace and deposited by chemical vapor infiltration deposition, wherein the deposition carbon source is methane, the deposition diluent is nitrogen, the methane is 80 L / min, the nitrogen is 10 L / min, the deposition temperature is 950 ° C, the deposition time is 192 h, the deposition pressure is 20 KPa, and the density after deposition is 1.2 g / cm 3 Deposition materials;
[0111] (2) immersing the above-mentioned deposited material in an impregnation solution, leaving it to stand for 2 hours in a vacuum environment at room temperature, and then taking it out and drying it naturally for 1 hour to obtain an impregnated material; wherein the impregnation solution includes 9000g of furan resin emulsion, 900g of KH560, 80g of yttrium oxide, 1000g of diethylenetriamine, 1500g of silicon powder, 1500g of silicon carbide powder and 200g of ethanol;
[0112] (3) The impregnated material was placed in a hot press for curing at a temperature of 330°C, a pressure of 5 MPa, and a time of 1 h to obtain a density of 1.8 g / cm 3 The curing material;
[0113] (4) The solidified material was then placed in a high-temperature furnace with nitrogen as the protective atmosphere at 900°C and 300 Pa for 4 hours for carbonization treatment to obtain a density of 1.5 g / cm 3 Carbonized materials;
[0114] (5) The carbonized composite material is machined to form bolt holes and positioning holes on the surface according to the aperture size requirements of the brake disc, and a cooling channel is milled on the outer ring, leaving a machining allowance of 2 mm in the thickness direction to obtain a brake disc blank;
[0115] (6) The above brake disc blank is placed in a graphite crucible and covered with silicon powder, the mass of which is 2.5 times that of the brake disc blank. The crucible is then placed in a high-temperature furnace and kept at 1700°C for 3 hours under vacuum for siliconization treatment to obtain a density of 2.6 g / cm 3 Carbon ceramic brake discs.
[0116] Example 6
[0117] The same as Example 1, except that the nitrogen is replaced by hydrogen. The density of the deposited material is 0.7 g / cm 3 The density of the cured material is 1.3 g / cm 3 , the density of the carbonized material is 1.1g / cm 3 The density of carbon ceramic brake disc is 1.9g / cm 3 .
[0118] Example 7
[0119] The same as Example 1, except that the preform A is changed to preform B. The density of the deposited material is 0.4 g / cm 3 , the density of the cured material is 0.8g / cm 3 , the density of the carbonized material is 0.6g / cm 3 The density of carbon ceramic brake disc is 1.2g / cm 3 .
[0120] Example 8
[0121] The same as Example 1, except that the hot pressing temperature of the curing treatment is 200°C. The density of the deposited material is 0.6 g / cm 3 The density of the cured material is 1.3 g / cm 3, the density of the carbonized material is 1.0g / cm 3 The density of carbon ceramic brake disc is 1.8g / cm 3 .
[0122] Comparative Example 1
[0123] The same as Example 1, except that KH550 in the impregnation solution is omitted. The density of the deposited material is 1.0 g / cm 3 The density of the cured material is 1.6 g / cm 3 The density of the carbonized material is 1.3 g / cm 3 The density of carbon ceramic brake disc is 2.0g / cm 3 .
[0124] Comparative Example 2
[0125] The same as Example 1, except that the rare earth oxide in the impregnation solution is omitted. The density of the deposited material is 1.0 g / cm 3 The density of the cured material is 1.6 g / cm 3 The density of the carbonized material is 1.35 g / cm 3 The density of carbon ceramic brake disc is 2.0g / cm 3 .
[0126] Comparative Example 3
[0127] The same as Example 1, except that steps 2-4 are omitted. The density of the deposited material is 1.0 g / cm 3 The density of carbon ceramic brake disc is 1.8g / cm 3 .
[0128] Test Example 1
[0129] XRD was used to analyze the sample and test the components and mass content of the carbon ceramic brake disc. The test results are shown in Table 1.
[0130] Table 1
[0131]
[0132]
[0133] Test Example 2
[0134] The compression resistance of carbon ceramic brake discs was tested according to GB / T 34559, the bending resistance of carbon ceramic brake discs was tested according to GB / T 6569, and the interlaminar shear performance of carbon ceramic brake discs was tested according to ASTM D2344 / D2344M-13. The test results are shown in Table 2:
[0135] Table 2
[0136]
[0137]
[0138] By comparing Example 1 and Example 6, it can be seen that the mechanical properties of the carbon ceramic brake disc are significantly better when nitrogen is used as the diluent gas than when hydrogen is used. This may be because hydrogen has an inhibitory effect on the pyrolysis reaction of the deposited carbon source, resulting in a decrease in the carbon deposition efficiency. Nitrogen is an inert gas and has no inhibitory effect on the pyrolysis reaction of the deposited carbon source. When nitrogen is used as the diluent gas, the carbon deposition efficiency of the deposition treatment is higher, and the amount of carbon deposited in the same time is large, so the carbon shell coated on the surface of the preform carbon fiber is thicker, which can more effectively protect the carbon fiber during the siliconization process, thereby preventing the carbon fiber from being damaged.
[0139] By comparing Example 1 and Example 7, it can be seen that the present invention can use a low-density preform to prepare a carbon ceramic material with good mechanical properties. The preform is the matrix of the carbon ceramic brake disc, providing the carbon ceramic brake disc with basic enhanced and toughened mechanical properties. Within the scope defined by the present invention, the greater the density of the preform, the higher the carbon fiber content, and thus the better the compressive resistance, bending resistance and interlaminar shear performance of the prepared carbon ceramic material.
[0140] By comparing Example 1 and Example 8, it can be seen that within the scope of the present invention, increasing the hot pressing temperature during the curing process can improve the mechanical properties of the carbon-ceramic brake disc. This may be because the resin is more completely cured at high temperatures, the solvent and gas are completely volatilized, and there are no large pores and gaps during the carbonization process, so the formed material is more dense and has better mechanical properties.
[0141] By comparing Example 1 and Comparative Example 1, it can be seen that the addition of silane coupling agent can significantly improve the mechanical properties of carbon ceramic brake disc. This is because, on the one hand, the silane coupling agent added to the impregnation liquid can be evenly distributed on the preform. In the subsequent siliconization process, the silane coupling agent, as a silicon source, generates silicon carbide with the carbon on the preform (including deposited carbon and carbon generated by resin), which can not only improve the uniformity of silicon carbide distribution on the carbon ceramic brake disc, but also reduce the content of residual silicon on the brake disc after siliconization. On the other hand, the silane coupling agent can be used as an intermediate bridge, connecting silicon carbide, silicon powder, and rare earth oxide on one side and organic resin on the other side, which can enhance the bonding strength between silicon carbide, silicon powder, rare earth oxide and resin, avoid sedimentation of inorganic fillers, and effectively improve the high temperature resistance of the resin, thereby increasing the curing temperature, improving the curing effect, and ensuring that the preform can shrink evenly in the subsequent curing and carbonization process, without cracking, deformation, bubbling and large pores, and ensuring the compactness of the carbon ceramic brake disc.
[0142] By comparing Example 1 and Comparative Example 2, it can be seen that rare earth oxides, as sintering aids for silicon carbide, can improve the densification degree of silicon carbide. The higher the densification degree of silicon carbide, the higher the strength and hardness of silicon carbide, and the more strength it can provide for the carbon-ceramic brake disc. Therefore, rare earth oxides can significantly improve the compressive properties, bending properties and interlaminar shear properties of carbon-ceramic brake discs. In Comparative Example 2, no rare earth oxides were added, and the densification degree of silicon carbide decreased during the siliconization process, which reduced the strength of silicon carbide, thereby causing the mechanical properties of the carbon-ceramic brake disc to decrease.
[0143] By comparing Example 1 with Comparative Example 3, it can be seen that the carbon ceramic material obtained by directly machining and siliconizing the preform after the deposition treatment has a small density and poor mechanical properties. This is because the pyrolytic carbon generated in the deposition treatment is not enough to provide sufficient carbon source to react with silicon powder. In the siliconizing operation, after the silicon powder reacts with the pyrolytic carbon, it continues to react with the carbon fibers in the preform, damaging the carbon fibers and reducing the mechanical properties of the carbon ceramic brake disc.
[0144] Test Example 3
[0145] The cured materials prepared in Examples 1-8 and Comparative Example 1 were subjected to a weight loss test according to the GB / T 27761-2011 method. The diameter of the cured material test sample was 30 mm, the thickness was 10 mm, and the test temperature was 350° C. The test results are shown in Table 3.
[0146] Table 3
[0147]
[0148]
[0149] It can be seen from Table 3 that the weight loss rate of the solidified material obtained after adding the silane coupling agent to the impregnation solution is below 3 wt %, and the weight loss rate of the solidified material in Comparative Example 1 without adding the silane coupling agent is much greater than that of Examples 1-8.
[0150] By comparing Example 1 and Comparative Example 1, it can be seen that the silane coupling agent can significantly improve the high temperature resistance of the resin, and can prevent the resin from decomposing during curing, thereby helping to improve the high temperature stability of the carbon-ceramic brake disc.
[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A carbon ceramic material, characterized in that: The carbon ceramic material comprises: 25-40wt% carbon, 60-70wt% silicon carbide, 0.5-3.5wt% residual silicon, and 1-3wt% rare earth oxide; The carbon ceramic material has a compressive strength of 190-270 MPa, a bending strength of 160-250 MPa, and an interlaminar shear strength of 60-95 MPa.
2. The carbon ceramic material according to claim 1, wherein: The rare earth oxide is selected from one or more of cerium oxide, yttrium oxide, lanthanum oxide, neodymium oxide, praseodymium oxide, and samarium oxide, preferably cerium oxide.
3. The carbon ceramic material according to claim 1 or 2, wherein: The carbon ceramic material has a compressive strength of 250-265 MPa, a bending strength of 240-250 MPa, and an interlaminar shear strength of 85-90 MPa.
4. The carbon ceramic material according to any one of claims 1 to 3, wherein: The density of the carbon ceramic material is 1.2-2.8 g / cm 3 , preferably 2.1-2.3 g / cm 3 .
5. A method for preparing a carbon ceramic brake disc, characterized in that: The method comprises the following steps: (1) performing a deposition process on the preform to obtain a deposition material; (2) impregnating the deposited material in an impregnation liquid to obtain an impregnated material; wherein the impregnation liquid contains a silane coupling agent and a rare earth oxide; (3) curing the impregnated material to obtain a cured material; (4) carbonizing the solidified material to obtain a carbonized material; (5) machining the carbonized material to obtain a brake disc blank; (6) The brake disc blank is mixed with silicon powder and then subjected to siliconizing treatment to obtain a carbon ceramic brake disc.
6. The preparation method according to claim 5, wherein: The density of the preform is 0.1-0.6 g / cm 3 , preferably 0.2-0.3 g / cm 3 ; Preferably, the preform is selected from carbon fiber cloth, which is formed by alternately laying a single layer of non-woven cloth and a mesh tire through a step-by-step needle punching method; wherein the number of layers of the alternately laid layers is 30-80 layers, preferably 40-60 layers; Preferably, the deposition process is selected from chemical vapor infiltration deposition; Preferably, the operating conditions of the chemical vapor infiltration deposition method include: the deposition carbon source is selected from one or more of methane, propane, and propylene, preferably methane; Preferably, the deposition diluent gas is selected from nitrogen and / or argon, preferably nitrogen; Preferably, the flow rate of the deposited carbon source is 30-80 L / min, preferably 45-65 L / min; the flow rate of the deposited dilution gas is 5-25 L / min, preferably 10-15 L / min; Preferably, the operating conditions of the chemical vapor infiltration deposition method also include: the number of depositions is 1, the deposition temperature is 900-1200°C, preferably 1050-1080°C; the deposition pressure is 5-30KPa, preferably 5-10KPa; the deposition time is 50-200h, preferably 90-150h.
7. The preparation method according to claim 5 or 6, wherein: The silane coupling agent is selected from one or more of methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, methylethyldiethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3,4-epoxycyclohexylmethyltrimethoxysilane, and 3,4-epoxycyclohexylmethyltriethoxysilane; Preferably, the rare earth oxide is selected from one or more of cerium oxide, yttrium oxide, lanthanum oxide, neodymium oxide, praseodymium oxide, and samarium oxide; Preferably, the impregnation liquid further comprises a resin, a curing agent, silicon powder, silicon carbide powder and a solvent; wherein the resin is selected from one or more of phenolic resin emulsion, furan resin emulsion and epoxy resin emulsion, the curing agent is selected from one or more of urotropine, ethylenediamine and diethylenetriamine, and the solvent is selected from ethanol and / or ethylene glycol; Preferably, the impregnation liquid contains, by mass, 9000 parts of resin, 400-1000 parts of silane coupling agent, 50-300 parts of rare earth oxide, 700-1100 parts of curing agent, 900-1600 parts of silicon powder, 900-1600 parts of silicon carbide powder and 100-300 parts of solvent; Preferably, the impregnation is carried out at room temperature and under vacuum, and the impregnation time is 1-4 hours, preferably 1.5-2.5 hours; Preferably, after the impregnation is completed, the deposited material is taken out from the impregnation liquid and dried naturally to obtain an impregnated material.
8. The preparation method according to any one of claims 5 to 7, wherein: The curing treatment is carried out under hot pressing conditions; wherein the hot pressing temperature is 200-350°C, preferably 250-300°C; the hot pressing pressure is 5-15MPa, preferably 8-12MPa; the hot pressing time is 1-3h, preferably 1.5-2.5h; Preferably, the carbonization treatment is carried out under the protection of an inert gas; wherein the inert gas is preferably nitrogen; Preferably, the operating conditions of the carbonization treatment include: carbonization temperature of 800-1000°C, preferably 850-950°C; carbonization pressure of 100-500Pa, preferably 200-400Pa; carbonization time of 2-6h, preferably 3.5-4.5h.
9. The preparation method according to any one of claims 5 to 8, wherein: The particle size of the silicon powder is 10-100 μm, preferably 30-60 μm; the purity of the silicon powder is ≥ 98%, preferably 99-99.9%; Preferably, the mass of the silicon powder is 1-2.5 times that of the brake disc blank, preferably 1-1.5 times; Preferably, the mixing is to bury the brake disc blank in the silicon powder; Preferably, the operating conditions of the siliconizing treatment include: the siliconizing treatment temperature is 1450-1800° C., preferably 1550-1650° C.; the siliconizing treatment time is 1-6 hours, preferably 2-3 hours.
10. A carbon-ceramic brake disc prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
A method for preparing carbon ceramic brake discs
CN109095929B
A rapid preparation method for brake materials based on polycarbosilane modification
CN109437955B